Analisis Korelasi Pre Eklampsia Dalam Kehamilan Dengan Kejadian Asfiksia Neonatorum - Nurul Auliya Kamila (JURNAL KEBIDANAN, 2021)
Asphyxia neonatorum is the failure of the newborn to breathe spontaneously and regularly, causing further disturbances. The onset of asphyxia in infants with pre-eclamptic mothers is due to high blood pressure causing reduced blood delivery to the placenta, this will reduce the supply of oxygen and food for the baby. As a result, the baby's development is slow, and intrauterine hypoxia occurs. The purpose of this study was to determine the correlation between pre-eclampsia in pregnancy and the incidence of asphyxia neonatorum in the NICU Room of the Mataram City Hospital, NTB in 2020. The research method used in this study was analytical correlational with a case control design with a retrospective time approach. The population is the data of all women giving birth in the NICU Room of Mataram City Hospital in 2020 as many as 1,098 people. The sampling technique used was systematic random sampling so that the number of samples obtained was 124 samples. The tools used are medical records. The statistical analysis used was the chi square test. The results showed that of the 124 samples studied, the neonatal asphyxia infants in mothers with pre-eclampsia were 39 (62.9%) compared to 23 (37.1%) non-preeclamptic mothers, the results of the probability value (p value) = 0.000 <α 0.05, by itself Ho is rejected, which means that there is a relationship between pre-eclampsia and newborn asphyxia at the Mataram City Hospital. So it can be concluded that, mothers who experience preeclampsia tend to have neonatal asphyxia. It is recommended that health workers at the Mataram City Hospital to further improve the quality of health services to the community, especially mothers giving birth, to keep their health checked at the health service place so that the risk of pre-eclampsia can be prevented.